Knowledge on lead exposure among Paint workers in Kirtipur Municipality, Nepal (International Journal of Occupational Safety and Health, 2025)
Introduction: Lead exposure is a serious threat to public health. Among various occupational groups, paint workers are at increased risk to lead exposure. This study aims to assess the knowledge on lead exposure, identify symptoms of lead toxicity and to estimate the blood hemoglobin level among paint workers in Kirtipur Municipality.Methods: Cross-sectional study design was used among 108 paint workers having at least 2 years of exposure. Data collection period was from June-August 2024. Data were collected using convenient sampling through interviews. Semi-structured questionnaires were used as a tool for data collection. Study has been approved by ethics committee. Data entry and analysis was done in SPSS. Bivariate analysis was done using chi-square test.Results: The mean age ± SD of the participants was 37.61 ±9.75 years. The mean years of exposure was 15.27 ±8.87 years, and mean duration of working was 9.39 ±2.07 hours/day. Headache was the most common symptoms of lead toxicity. Only 10 (9.3%) of the paint workers had good knowledge on lead exposure. Those who have taken formal training on hazards and safety measures have good knowledge on lead exposure and the association was also statistically significant (P≤0.001). However, age, work duration, work experience, and education did not show any significant association. On blood hemoglobin estimation, 28(25.9%) were found to be anemic.Conclusion: Study shows that only 9.3% of paint workers have good knowledge on lead exposure. So, awareness program on lead exposure and regular training programs on hazards and safety measures should be conducted.